Peningkatan Keterampilan Membaca Permulaan Melalui Media Audio Visual Pada Kelas I UPTD SDN 145 Inpres Pampangan - Haslinda Haslinda; Musdalifa Musdalifa; Rezky Aulia Yusuf (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research aims to improve students' initial reading skills using audio-visual media in class I UPTD SDN 145 Inpres Pampangan. This research is Classroom Action Research, the subject of this research is class 1, totaling 30 students consisting of 18 boys and 12 girls. This research was carried out for 3 weeks. The implementation of this action was carried out during three 3 teaching and learning process meetings and at every third meeting there was a learning evaluation results test. This research was carried out as part of the Teaching Profession Strengthening (P2K) activities which started on September 11 2023 for the 2023/2024 academic year. The results of the research show that during the learning process there is a change in students' attitudes during the learning process in accordance with the results of observations, namely by applying reading skills through audio-visual media assisted by image media, it can increase students' self-confidence to ask both the teacher and their friends about material they don't know. understandable and can increase student attendance, and improve student reading skills with audio-visual media. So, beginning reading skills through audio-visual media are suitable for use in this class. This can be seen from the increase in learning outcomes for class I students at UPTD SDN 145 Inpres Pampangan, after learning initial reading skills through audio-visual media.